(untitled) (Bulletin of Armenian Libraries, 2015)
History of establishment of the first Armenian periodical in Egypt ՛՛Armaveni" is described. Being established in 1865 in Cairo, only 4 issues of the newspaper were published. The reasons of the short life of the newspaper are provided.